Neuronal Sprouting and Reorganization in Bone Tissue Infiltrated by Human Breast Cancer Cells - Hansen, Rie B.; Sayilekshmy, Manasi; Sørensen, Michala S.; Jørgensen, Astrid H.; Kanneworff, Ida B.; Bengtsson, Emma K. E.; Grum-Schwensen, Tomas A.; Petersen, Michael M.; Ejersted, Charlotte; Andersen, Thomas L.; Andreasen, Christina M.; Heegaard, Anne-Marie (Frontiers in Pain Research, 2022)
Background: Pain is a common complication for patients with metastatic bone disease. Animal models suggest that the pain, in part, is driven by pathological sprouting and reorganization of the nerve fibers innervating the bone. Here, we investigate how these findings translate to humans. Methods: Bone biopsies were collected from healthy volunteers (n=7) and patients with breast cancer and metastatic bone disease (permissions H-15000679, S-20180057 and S-20110112). Cancer-infiltrated biopsies were from patients without recent anticancer treatment (n=10), patients with recent anticancer treatment (n=10), and patients with joint replacement surgery (n=9). Adjacent bone sections were stained for 1) protein gene product 9.5 and CD34, and 2) cytokeratin 7 and 19. Histomorphometry was used to estimate the area of bone marrow and tumor burden. Nerve profiles were counted, and the nerve profile density calculated. The location of each nerve profile within 25 µm of a vascular structure and/or cancer cells was determined. Results: Cancer-infiltrated bone tissue demonstrated a significantly higher nerve profile density compared to healthy bone tissue. The percentage of nerve profiles found close to vascular structures was significantly lower in cancer-infiltrated bone tissue. No difference was found in the percentage of nerve profiles located close to cancer between the subgroups of cancer-infiltrated bone tissue. Interestingly, no correlation was found between nerve profile density and tumor burden. Conclusions: Together, the increased nerve profile density and the decreased association of nerve profiles to vasculature strongly suggests that neuronal sprouting and reorganization occurs in human cancer-infiltrated bone tissue.